2019
DOI: 10.3126/nmcj.v21i1.24844
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Errors and its Associated Factors among Undergraduate Medical Students in Kathmandu

Abstract: Refractive error is a defect in the optical system of the eye which prevents light from being brought to a single point focus on the retina, thus reducing normal vision. This optical defect is the second most common cause of visual impairment globally as well in Nepal. At present, there are 285 million visually impaired people in the world. An estimated 4 out of 5 visual impairment (80%) can be prevented or cured, uncorrected refractive errors are the leading cause (42%) followed by cataract (33%). A descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
0
1
Order By: Relevance
“…7 -12 Refractive error was the most common ocular morbidity reported in our study, occurring in 60 (52.2 %) students. This study concurs with a study from Nepal which reported a prevalence of 51.4% of refractive error among medical students, 32 and between 54% to 74% from studies in India. [22][23][24][25][26][27][28][29][30][31] Studies by Nwosu et al 13 and Maurya et al 16 reported a prevalence of refractive error as 63.0% and 39.8% respectively.…”
Section: Discussionsupporting
confidence: 92%
“…7 -12 Refractive error was the most common ocular morbidity reported in our study, occurring in 60 (52.2 %) students. This study concurs with a study from Nepal which reported a prevalence of 51.4% of refractive error among medical students, 32 and between 54% to 74% from studies in India. [22][23][24][25][26][27][28][29][30][31] Studies by Nwosu et al 13 and Maurya et al 16 reported a prevalence of refractive error as 63.0% and 39.8% respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Our results were higher than reported in some previous studies including study conducted in Malaysia showed a prevalence of refractive errors among university students by 32.24%(Gopalakrishnan et al, 2011), while Salih, (2018) showed that 33% of the students in Al-Mustansiriya Medical College, Iraq had refractive errors. Moreover, our results were higher than reported in two studies conducted in India (48.3%, 47.4%)(Patel et al, 2019; Kshatri et al, 2016), Nepal (51.4%)(Rizyal et al, 2019) and Pakistan (47%)(Parveen et al, 2016).…”
contrasting
confidence: 78%